Association of the hERG mutation with long-QT syndrome type 2, syncope and epilepsy - LI, GUOLIANG (Mol Med Rep, 2016)
Mutations in the human ether-à-go-go-related gene (hERG) are responsible for long-QT syndrome (LQTS) type 2 (LQT2). In the present study, a heterozygous missense mutation (A561V) linked to LQT2, syncope and epilepsy was identified in the S5/pore region of the hERG protein. The mutation, A561V, was prepared and subcloned into hERG-pcDNA3.0. Mutant plasmids were co-transfected into HEK-293 cells, which stably express wild-type (WT) hERG, in order to mimic a heterozygous genotype, and the whole-cell current was recorded using a patch-clamp technique. Confocal microscopy was performed to evaluate the membrane distribution of the hERG channel protein using a green fluorescent protein tagged to the N-terminus of hERG. A561V-hERG decreased the amplitude of the WT-hERG currents in a concentration-dependent manner. In addition, A561V-hERG resulted in alterations to activation, inactivation and recovery from inactivation in the hERG protein channels. Further evaluation of hERG membrane localization indicated that the A561V-hERG mutant protein was unable to travel to the plasma membrane, which resulted in a trafficking-deficient WT-hERG protein. In conclusion, A561V-hERG exerts a potent dominant-negative effect on WT-hERG channels, resulting in decreased hERG currents and impairment of hERG membrane localization. This may partially elucidate the clinical manifestations of LQTS patients who carry the A561V mutation.